Research methods for reading digital data in the digital humanities (Edinburgh University Press, 2016)
8 Knowing Your Crowd: An Essential Component to Crowdsourcing Research9 Fantasies of Scientificity: Ethnographic Identity and the Use of QDA Software; 10 Digital Network Analysis: Understanding Everyday Online Discourse Micro- and Macroscopically; 11 Dealing with Big Data; Notes on Contributors; Index. Research Methods for Reading Digital Data in the Digital Humanities; Copyright; Contents; Acknowledgements; 1 Introduction; 2 Matter Matters: The Effects of Materiality and the Move from Page to Screen; 3 Reading the Visual Page in the Digital Archive; 4 Paratextual Navigation as a Research Method: Fan Fiction Archives and Reader Instructions; 5 Data Mining and Word Frequency Analysis; 6 Reading Twitter: Combining Qualitative and Quantitative Methods in the Interpretation of Twitter ; 7 Reading Small Data in Indigenous Contexts: Ethical Perspectives. The first volume centred on the navigation and interpretation of digital material as research methods in the Humanities
Includes bibliographical references and index
Keywords: Humanities; Digital media; REFERENCE; Questions & Answers; Humanities; Research; Methodology; Digital Humanities; Data Mining; Methode